PROBLEMATIKA PEMBELAJARAN STATISTIKA PADA JURUSAN SOSIAL KEAGAMAAN KRISTEN - Jean Ilela (TANGKOLEH PUTAI, 2019)
The role of meaningful statistics is of increasing importance in today's world filled with data. Quoting the slogan of the Central Bureau of Statistics which carries the slogan "Data Educating the Nation", it is not wrong if Statistics learning is one of the important lessons in the world of education. The Statistics course itself is not only applied to exact science majors but has also been applied to Christian Religious Social majors. Statistics is a science that deals with how to analyze data, summarize and present data, analyze data with certain methods and implement the results of the analysis. Therefore, Statistics is a compulsory subject in almost all departement in preparation for preparation with research methodology. Factors that influence the learning process that can have positive and negative impacts. Statistics learning problems in the Department of Social Religious Christianity can reduce good classroom management and change the mindset of students and study habits. Both lecturers and students are able to show their best performance so that the learning process can run well so that it has an impact on the learning outcomes obtained. Among the solutions of the teacher is the presence of increased professionalism of educators that includes personal competence, pedagogical competence, professional competence and social competence.